How Should the Law Work? A Book Review “Biarkan Hukum Mengalir: Catatan Kritis Tentang Pergulatan Manusia dan Hukum”, Prof. Dr. Satjipto Rahardjo SH, PT Kompas Media Nusantara Jakarta, 2007, 158 pages, ISBN: 978-979-709-334-1 - Kurniawan, Ade Mirza (JILS (Journal of Indonesian Legal Studies), 2021)
In this book, the author conveys criticism and suggestions regarding the development of law that has the dimension of humanity and the values ​​of true justice. Starting from the meaning of order, local communities with their specific but effective policies, to the idea of ​​legal certainty related to the status-quo. Delivered in a light and flowing language, this book needs to be read by lecturers and law students, observers, and researchers in the field of social politics, as well as anyone who cares about the value of justice and humanity. This book “mistrust” human flashiness in creating and carrying out the law, as well as breaking and tearing it down. Delivered in a light and flowing language, this book needs to be read by lecturers and law students, observers and researchers in the field of social politics, as well as anyone who cares about the value of justice and humanity.